Design and implementation of a single-phase five-level inverter using a DC Source with voltage balancer on capacitor - Leonardus Heru Pratomo; Slamet Riyadi (International Journal of Power Electronics and Drive Systems (IJPEDS), 2021)
The global use of renewable energy resources has led to the design and development of high performance, efficient, controllable, and cheap multilevel inverters, which act as a solution to the numerous power deficiencies. However, in terms of control, these multilevel inverters are often associated with DC sources and complexity. Therefore, this research designed a single-phase five-level inverter using a DC source, with a novel sinusoidal pulse-width-modulated (SPWM) control scheme. The system consists of a Flying Capacitor DC-DC Converter and H-Bridge Inverter (FCDCDC-HBI). A single absolute reference signal and the phase-shifted triangular carrier were used to generate SPWM to enhance the capacitor voltage balance. The designed inverter is capable of producing five levels of output voltage levels, namely Vi, Vi/2, 0, −Vi/2, and −Vi from a DC supply, thereby reducing the overall cost and complexity of the SPWM system. This research also produced a detailed operation principle of the proposed system, which was verified through simulation and implemented using a prototype. Finally, hardware implementation results are presented to check the performance of the inverter.